2021
DOI: 10.3389/fcell.2021.642352
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in Vascular Endothelial Cells, Angiogenesis, and Tumor Progression: An Update and Prospective

Abstract: The Notch signaling pathway plays an essential role in a wide variety of biological processes including cell fate determination of vascular endothelial cells and the regulation of arterial differentiation and angiogenesis. The Notch pathway is also an essential regulator of tumor growth and survival by functioning as either an oncogene or a tumor suppressor in a context-dependent manner. Crosstalk between the Notch and other signaling pathways is also pivotal in tumor progression by promoting cancer cell growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 207 publications
(188 reference statements)
1
104
0
Order By: Relevance
“…Furthermore, the crosstalk between BCSCs and arteriolar ECs via Notch signaling may contribute to changes in CSC phenotypes 7,63,70 , in which PKD-1 signaling-mediated arteriolar differentiation may be indispensable by development of an arteriolar niche. Although distinct vascular niches are likely needed to regulate BCSCs, we found that LPA/PKD-1 signaling-mediated DLL4 expression in the arteriolar ECs facilitates direct EC interaction with Notch1 + stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the crosstalk between BCSCs and arteriolar ECs via Notch signaling may contribute to changes in CSC phenotypes 7,63,70 , in which PKD-1 signaling-mediated arteriolar differentiation may be indispensable by development of an arteriolar niche. Although distinct vascular niches are likely needed to regulate BCSCs, we found that LPA/PKD-1 signaling-mediated DLL4 expression in the arteriolar ECs facilitates direct EC interaction with Notch1 + stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Notch1 activity plays a pivotal role in the stemness and progression of ER + BC [61][62][63] and ECs can interact with BC via the Notch1 pathway 7,63 , we tested whether PKD-1 signaling can impact Notch1 expression by transducing BC cells with PKD-1. Overexpression of PKD-1 signi cantly increased the expression of Notch1 at both mRNA and protein levels in BC cells (Figure 7C & D), along with an increased expression in CD44 and KLF4 (Figure 7E & F).…”
Section: Lpa/pkd-1 Signaling In Self-renewal Of Bcscsmentioning
confidence: 99%
“…Crosstalk between VEGF and other signaling pathways importantly contributes to tumor angiogenesis regulation, through the activation of alternative VEGF-dependent and VEGF-independent pathways [ 34 ]. Guanylyl cyclase C (GUCY2C), a receptor member of the family of guanyl cyclases, plays an important role in regulating intracellular cGMP levels, electrolyte homeostasis and cell proliferation in the intestine [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its overexpression has been associated with metastasis and poor prognosis in CRC patients [ 38 ]. On the other hand, the VEGF and Notch signaling pathways are two pivotal mechanisms in tumor angiogenesis [ 34 ]. In fact, placenta growth factor (PGF) is a ligand of the VEGF family that induces angiogenesis by both VEGF-independent and VEGF-dependent ways [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…When tumors grow to 1-2 mm in diameter, the inner cells of the tumor become hypoxic, which inhibits the degradation of the Hypoxiainducible factor 1-alpha (HIF-1α). Hypoxia-Thus, HIF-1α is increased and binds to the Response Element (HRE) region of genes involved in angiogenesis, such as the VEGF-expressing gene, so by this way, the expression of VEGF is increased [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%